The Impact of Capital Regulations on Bank Margins of ASEAN Banking Sector - Fatin Nur Hidayah Taib Khan,; Nurhafiza Abdul Kader Malim,; Tajul Ariffin Masron,; Rossazana Ab Rahim, (Asian Academy of Management Journal of Accounting and Finance, 2023)
Basel Committee on banking supervision (BCBS) has issued Basel which requires the banks to comply with the minimum capital requirement after the crisis. Nevertheless, whether the requirement imposes impact the banking sector which comprises a dual banking system, in a positive manner is still questionable. Given the higher capital costs from the strict capital requirements, banks are being forced to raise bank margins. This study investigates the effect of capital regulations on conventional and Islamic banks’ margins covering the ASEAN banking system from 2009 to 2017. The empirical analysis uses dynamic panel data frameworks to reveal several factors affecting bank margins. Overall, the results suggest that the total regulatory capital ratio helps reduce the margins of conventional banks but does not influence the margins of Islamic banks. As for the Tier-1 capital ratio, the variable increases the Islamic bank margins but does not significantly affect conventional bank margins. Based on the analysis results, regulators of conventional banks need to impose capital requirements as suggested by Basel III to reduce bank margins. Meanwhile, as for Islamic banks, the bank margins can be reduced if regulators can introduce a separate set of requirements tailored explicitly for Islamic banks.